Equine Assisted Activities to help Minors With Autism Spectrum Disorder. A Literature Review - Axpe, Inge (2023)
Introduction, Autism Spectrum Disorder (ASD) lacks a definitive treatment, although Animal Assisted Activities, especially with horses, stand out as an alternative for its symptoms. Objective, To review the research on Equine Assisted Therapy and its efficacy in working with children with ASD. Analysis, Previous literature was reviewed between 2012 and 2020 in various databases (MEDLINE, psycINFO, PsycArticles, Psychology and Behavioral Sciencies Collection, Psicodoc and ERIC), establishing as search and analysis criteria that the publications were refereed, had the full text for subsequent reading and coding, and had been published from 2012 onwards. Taking into account all of the above, 16 interventions carried out between 2012 and 2019 were finally included. Results, From the articles obtained and reviewed, it was found that therapeutic riding predominates and significant improvements were observed in the participating children in aspects such as hyperactivity, irritability, motor skills (improving the performance of tasks autonomously) and even certain social aspects. Conclusions, despite the benefits observed, it is also clear that it is difficult to draw conclusions and systematize the results, due to the great variability of instruments and measures used in the different studies. Recommendations, Although therapeutic riding seems to be beneficial for working with children with ASD, more reviews and especially meta-analyses are needed to know its true effect.